Policy landscape analysis for fruits and vegetables in four low- and middle-income countries through a food systems approach - Elaine Q. Borazon; Samali Perera; Nestor Alokpaï; Mario Sibamenya Venance; Erica Reeve; Jody Harris; Takwa Tissaoui; Anne Marie Thow (PLoS ONE, 2025)
Low fruit and vegetable intake is a significant nutritional issue in low- and middle-income countries, where resolving all forms of malnutrition remains a pressing challenge. Nutritional status is influenced by many dietary factors, and enhancing fruit and vegetable consumption offers significant health benefits and contributes to overall dietary quality. The study aimed to examine the policy landscape for fruits and vegetables across the food system in four low-middle income countries (Benin, Sri Lanka, Tanzania, the Philippines) and identify opportunities to strengthen food systems policies to enhance fruit and vegetable consumption as part of a comprehensive strategy to improve nutrition outcomes. A comparative qualitative analysis of policy documents (n = 14 [Benin], 18 [Sri Lanka], 30 [Tanzania], 55 [the Philippines] relevant to fruits and vegetables at the national and subnational levels, framed by a food systems framework, was conducted. A modified SWOT analysis was then conducted to formulate strategic policy recommendations to improve consideration of fruits and vegetables in policies tackling food system aspects. The analysis revealed specific opportunities for strengthening policy prioritization of fruits and vegetables across the food system such as multisectoral collaboration, policy integration between the national and subnational level, sustainability and resilience, and inclusion and equity. By addressing factors influencing fruit and vegetable intake within a dynamic food system, these countries and others facing challenges to the consumption of fruits and vegetables can effectively promote diet quality, improve food security, and address all forms of malnutrition through better policy design and particularly implementation.